(untitled) (Research, Society and Development, 2021)
Honeybees are the insect most used for pollination purposes due to its efficient characteristics for this function, which reflects in positive aspects for both nature and man. The expansion of agriculture and the development of agrochemicals to combat pests has had negative impacts on honeybee health, causing its disappearance around the world. This research aimed to evaluate the effects of honeybee exposure to the neonicotinoid insecticide thiamethoxam on its survival rate, as well as on morphological and histological changes in the midgut of adult workers from the F4 generation of Apis mellifera queens tolerant to thiamethoxam and non-tolerant worker honeybees. After the bioassays, the midgut was removed for morphological evaluation. The results showed that F4 bees were more tolerance to thiamethoxam and exhibited less significant morphological changes when compared to the non-tolerant control group.